EFEKTIVITAS PROBLEM BASED LEARNING BERBANTUAN WORDWALL TERHADAP HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR SISWA KELAS IV SD - Aprilia Zahra; Akbar, M. Taheri; Kuswidyanarko, Arief (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of the application of the Problem Based Learning (PBL) learning model assisted by Wordwall on the mathematics learning outcomes in the material of flat shapes of grade IV students of SD Negeri 232 Palembang. This study uses a quantitative approach with an experimental design Posttest Only Control Group Design. The study population was all grade IV students of SD Negeri 232 Palembang. The research sample consisted of class IV A totaling 26 students as the control class and class IV B totaling 24 students as the experimental class. Data collection was carried out through a written test, the results of data analysis showed that the average posttest score of the experimental class was 86.08, while the average posttest score of the control class was 77.08. Based on the results of the hypothesis test using the t-test, a significance value (2-tailed) of 0.000 <0.05 was obtained. Thus, it can be concluded that there is an effectiveness of the application of the Problem Based Learning (PBL) learning model assisted by Wordwall on the mathematics learning outcomes in the material of flat shapes of grade IV students of SD Negeri 232 Palembang.